Respostas

2013-09-27T06:18:32-03:00
A.-3x+2=0              b.-3x+2=11
 a.  -3x=-2  x(-1)     b.      -3x=11-2        c.-3x+2=-1/2
    3x=2                           -3x=9 x(-1)        -6x+4=1
      x=2/3                         3x=-9               -6x=1-4
                                         x=-9/3            -6x=-3  x(-1)
                                         x=-3                6x=3
                                                                  x=3/6
                                                                  x=1/2
  
1 5 1